Effects of Preparation Temperature and Liquid-Solid Lipid Composition to Curcumin-Nanostructured Lipid Carrier Characteristics Fabricated by Microfluidic Technique - Ridho Arief Al Rasyid; Diah Mardiana; Ridho Firmansyah; Zubaidah Ningsih (Chemistry Department, The University of Brawijaya, 2023)
Nanostructured Lipid Carriers (NLC) are lipid-based carrier that uses a combination of liquid and solid lipids which is believed to deliver a higher amount of active substance to the human body. This study aimed to obtain the best formulation and evaluate the stability of curcumin-loaded NLC (C-NLC) using microfluidic technique at temperature of 40oC and 60oC with the ratios of liquid:solid lipids were 2 : 1 ; 3.5 : 1 ; 4 : 1 ; 6 : 1% w/w. Our results showed that the increase of process temperature and liquid lipid concentration reduced particle size. There was a non-linear relationship between lipid ratio and temperature to encapsulation percentage. At ratio of soybean oil:stearic acid 6 : 1 and, at 40°C, particles size (PS) obtained was 143.87 ± 3.36 nm, polydispersity index (PDI) obtained was 0.44 ± 0.01, zeta potential (ZP) obtained was -33.3 ± 6.53 mV with encapsulation percentage of 20.62%. At the same ratio at 60°C, the PS obtained was 60.21 ± 2.55 nm, PDI obtained was 0.72 ± 0.03, ZP obtained was -26.10 ± 1.83 mV and encapsulation percentage of 31.45%. Stability test showed that C-NLC produced at 60°C was more stable since the change of particle size and pH were lower than C-NLC produced at 40°C.